Association of preoperative infections, nasal Staphylococcus aureus colonization and gut microbiota with left ventricular assist device outcomes. (31st May 2021) - Yuzefpolskaya, Melana; Lumish, Heidi S.; Javaid, Azka; Cagliostro, Barbara; Mondellini, Giulio M.; Bohn, Bruno; Sweat, Austin; Onat, Duygu; Braghieri, Lorenzo; Takeda, Koji; Naka, Yoshifumi; Sayer, Gabriel T.; et al.
Abstract: Aims: Infections are common following left ventricular assist device (LVAD) implantation and predict adverse events. Infections are frequent prior to LVAD implantation although their impact on postoperative outcomes remains unknown. Gut and nasal microbial imbalance may predispose to mucosal colonization with pathogens. Herein, we investigated the predictive role of pre‐LVAD infections, and explored the association of nasal Staphylococcus aureus (SA) colonization and gut microbiota, on postoperative outcomes. Methods and results: Overall, 254 LVAD patients were retrospectively categorized based on pre‐LVAD infection status: Group 1, bacterial/fungal bloodstream infection (BSI); Group 2, other bacterial/fungal; Group 3, viral; and Group 4, no infection. In a subset of patients, nasal SA colonization ( n  = 140) and pre‐LVAD stool ( n  = 25) were analysed using 16S rRNA sequencing. A total of 75 (29%) patients had a pre‐LVAD infection [Group 1: 22 (29%); Group 2: 41 (55%); Group 3: 12 (16%)]. Pre‐LVAD BSIs were independent predictors of 1‐year postoperative mortality and infections [Group 1 vs. 4: hazard ratio (HR) 2.70, P  = 0.036 vs. HR 1.8, P  = 0.046]. In an unadjusted analysis, pre‐LVAD infections other than BSIs, INTERMACS profile ≤2, higher serum creatinine, lower serum albumin and nasal SA colonization were also significantly associated with postoperative infections. Patients with early post‐LVAD infections exhibited decreased microbial diversity ( P  < 0.05). Conclusions: Pre‐LVAD infections are common. BSIs independently predict postoperative mortality and infections. Additional studies are needed to confirm our findings that pre‐LVAD SA nasal colonization and gut microbial composition can help stratify patients' risk for infectious complications after LVAD implantation. Abstract : Association of pre‐left ventricular assist device (LVAD) infections, nasal Staphylococcus aureus colonization and gut microbiome dysbiosis with outcomes in LVAD patients. Infections are frequent in advanced heart failure (HF) patients before LVAD implantation, are mainly bacterial [blood stream infections (BSIs), urinary tract infections (UTIs) and pneumonias] ( A ) and associated with increased postoperative mortality and infections ( B, C ). Our exploratory analyses indicate that nasal S. aureus colonization ( D ) and altered gut microbial composition ( E ) are associated with increased risk of infection after LVAD implantation. ESV, exact sequence variant.